A Study of the Photoelectrochemical Etching of n-GaN in H3PO4 and KOH Electrolytes. (1st January 2020) - Heffernan, C.; Lynch, R. P.; Buckley, D. N.
Abstract : We investigated the photoelectrochemical etching of n-GaN in H3 PO4 and KOH as a function of electrolyte concentration, potential and light intensity. Etch rates measured by stylus profilometry were compared with coulometric and amperometric values. In both electrolytes, etch rates increased with concentration, reaching a maximum at 3.0 mol dm −3 and decreasing at higher concentrations. The increase in etch rate with concentration of either H3 PO4 or KOH reflects the amphoteric nature of gallium and the decrease above 3.0 mol dm −3 is attributed to common-ion effects. Profilometric etch rates were lower than coulometric and amperometric etch rates reflecting formation of a surface film. SEM and profilometry demonstrated that thick surface films are formed at lower concentrations. Etch rates increased linearly with light intensity indicating a carrier-limited etching regime: a quantum efficiency of 57.6% was obtained. At light intensities greater than ∼35 mW cm −2 the etch rates showed evidence of saturation. AFM and SEM images of the etched GaN surfaces showed a distinctive ridge-trench structure with a hexagonal appearance. Photoluminescence spectra of the etched GaN show a significant increase in the defect-related yellow luminescence peak suggesting correlation to the formation of the ridge structures, which may represent dislocations terminating at the surface.